ANALISIS PENERAPAN AKUNTANSI PERPAJAKAN TERHADAP DEPRESIASI ASET SEWA GUNA USAHA DENGAN HAK OPSI DITINJAU DARI SUDUT PANDANG PENYEWA PADA PT. SINAR CIPTA PERSADA SEJATI - Toweula, Azarya Anugrah; Tinangon, Jantje J.; Kalalo, Meily (Universitas Sam Ratulangi, 2018)
A lease is a financing activity in the form of the provision of capital goods either under a lease with a finance lease or an operating lease for use by the lessee for a specified period of time on a periodic basis. Lease do it by PT. Sinar Cipta Persada Sejati is lease with Capital Lease method. At the end of lease period, the company has authorities to buy lease asset. The purpose of this research is to know how the implementation of tax accounting to capital lease asset depreciation at PT. Sinar Cipta Persada Sejati as Lessee. This research use descriptive comparative method. The results of this research has proven that transaction of capital lease do it by PT. Sinar Cipta Persada Sejati has not applicable with tax rules, in depreciation problem the company only applied the commercial accounting rules, that is depreciation starts when the company get the capital lease asset and the basic of depreciation is the cost of the asset. The difference of commercial accounting anda tax accounting will be a fiscal correction of income taxes.Keywords: Tax Accounting, Lease, Capital Lease